Options for agricultural service cooperatives in a postsocialist economy: Evidence from Romania. (March 2020) - Wolz, Axel; Möllers, Judith; Micu, Marius Mihai
Almost three decades since the collapse of the socialist regime, Romania's farm structure is characterized by a distinct dual pattern. The far majority of farms is relatively small, while a small number manages about half of the total utilized agricultural area. Most farmers face significant constraints in creating viable farm businesses. When this is the case, it can be assumed that farmers will unite and establish agricultural service cooperatives (ASCs), as has been observed in many other parts of the world. In Romania, however, as in many other postsocialist economies, farmers tend to be reluctant to form or join formal organizations of mutual assistance. Yet there are signs of change, as first ASCs have recently been established. The objectives of this contribution are twofold: First, we discuss the major obstacles why ASCs did not develop after regime change. Second, we analyze the major reasons and influencing factors why private family farmers become more open to this type of formal organization in recent years. The analysis is based on a literature review, farm statistics, and qualitative in-depth interviews with farmers in 2018.